Proponents of gay marriage demonstrating - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows group of proponents of gay marriage demonstrating outside the Santa Clara County government services building at Day of Marriage demonstration. Demonstrators hold signs that read, "Marriage ban divides families", "Love is love", "Hate is not a family value", "Love does not discriminate", "Wanted, a son in law", " We want equa[l] righ[ts] not speci[al] rights", and "Marriage is a family value". Reverend Vaughn Beckman is standing at the far right in the front row. He is wearing dark clothing and a collar.